Petroleum geology of the Black Sea - Simmons, M. D.; Tari, G. C.; Okay, A. I. (Geological Society special publication ;, 2018)
The Black Sea remains one of the largest underexplored rift basins in the world. Future success is dependent on a better understanding of a number of geological uncertainties. These include reservoir and source rock presence and quality, and the timing of migration of hydrocarbons relative to trap formation. An appreciation of the geological history of the Black Sea basins and the surrounding orogens is therefore key. The timing of basin formation, uplift of the margins, and of facies distribution remain issues for robust debate. This text presents presents the results of 15 studies that relate to the tectono-stratigraphy and petroleum geology of the Black Sea. The methodologies of these studies encompass crustal structure, geodynamic evolution, stratigraphy and its regional correlation, petroleum systems, source to sink, hydrocarbon habitat and play concepts, and reviews of past exploration.